Starting anew in international investment law - M. Sornarajah (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
There is a crisis in international investment law brought about by rapid changes in the economic order resulting in movements of capital from erstwhile developing countries like China and India into developed ones. This is accentuated by the stances taken in investment treaty arbitration that restrict regulatory control. The reaction has been to bring about so called "balanced treaties" that neither secure investment protection nor bring about clear rules on regulatory control. There is a need for a new beginning.
Keywords: 330